Does size matter? Aspects (survival and seasonality) that influence birds with cranioencephalic trauma admitted at a wildlife rehabilitation center in Rio Grande do Sul, Brazil - Perin Marcon, Amanda; Gabriéli da Silva, Paloma; Rodrigues, Gabriela; Piasson Barletto, Ísis; Weschenfelder Teixeira de Carvalho, Kimberly; Westphal de Ataide, Michelli (Archives of Veterinary Science, 2024)
Birds with craniocephalic trauma (CET) show clinical signs such lack of proprioception, hypothermia, altered respiratory rates, fractures, and potential blindness. Treatment focuses on life support, including low-stimulus environments, analgesia, anti-inflammatory drugs, fracture immobilization, and patient stabilization through warmth, oxygenation, hydration, and soft food. Recovery time is uncertain, often resulting in death within days. Factors influencing recovery include injury severity, species size, treatment speed, presence of other diseases, and stress levels. We analyzed the species and their characteristics, occurrences periods, and outcomes of 265 birds of 60 species with CET received at the Wildlife Study Group at the University of Passo Fundo (GEAS-UPF) between 2015-2023. Most cases (72%) succumbed to death on average three days after admission, with small-sized birds having the highest mortality rate (86%). Passeriformes and Strigiformes were the most frequent orders, and the predator guild was the most affected.